Profile of Pulmonary Tuberculosis Patients with Type 2 Diabetes Mellitus in Pulmonary Department Dr. Soetomo General Hospital Surabaya - Ayu Rahmanita Putri Soetrisno; Rebekah Juniati Setiabudi; Laksmi Wulandari (Faculty of Medicine Universitas Airlangga, 2020)
Background: Pulmonary tuberculosis (TB) is the most important infectious disease, caused by Mycobacterium tuberculosis (MTB). Indonesia is the third country with the most prevalent TB cases in the world. Not all people who were exposed to MTB will become active TB, because the immune response is the main determinant. Immunocompromised person, such as patients who have type 2 diabetes mellitus (DM) as a comorbid are more prone to develop active TB infection. This study aimed to analyze the profile of pulmonary TB patients with type 2 DM in Pulmonary Department Dr. Soetomo General Hospital Surabaya.Methods: This was an observational descriptive study with a cross-sectional design. The research data were obtained from the medical records of TB patients with type 2 DM in Pulmonary Department Dr. Soetomo General Hospital Surabaya in January - December 2017.Results: Out of a total of 414 hospitalized patients, 74 patients with pulmonary TB were found with type 2 DM. Only 53 patients fulfilled the inclusion criteria. Gene Xpert results were sensitive (66.7%), previous TB treatment history (54.7%), unregulated type 2 DM (88.4%), RBG with the average of 311.83 mg/dl, PPBS with the average of 263.31 mg/dl, FBG with the average of 238 mg/dl, and HbA1C > 10% (68%).Conclusion: The majority of the patients of pulmonary TB with type 2 DM have average high blood glucose and unregulated DM.